Epigenetic signatures of childhood abuse and neglect: Implications for psychiatric vulnerability. (December 2016) - Cecil, Charlotte A.M.; Smith, Rebecca G.; Walton, Esther; Mill, Jonathan; McCrory, Eamon J.; Viding, Essi
Abstract: Childhood maltreatment is a key risk factor for poor mental and physical health. Recently, variation in epigenetic processes, such as DNA methylation, has emerged as a potential pathway mediating this association; yet, the extent to which different forms of maltreatment may be characterized by unique vs shared epigenetic signatures is currently unknown. In this study, we quantified DNA methylation across the genome in buccal epithelial cell samples from a high-risk sample of inner-city youth (n = 124; age = 16–24; 53% female), 68% of whom reported experiencing at least one form of maltreatment while growing up. Our analyses aimed to identify methylomic variation associated with exposure to five major types of childhood maltreatment. We found that: (i) maltreatment types differ in the extent to which they associate with methylomic variation, with physical exposures showing the strongest associations; (ii) many of the identified loci are annotated to genes previously implicated in stress-related outcomes, including psychiatric and physical disorders (e.g. GABBR1, GRIN2D, CACNA2D4, PSEN2) ; and (iii) based on gene ontology analyses, maltreatment types not only show unique methylation patterns enriched for specific biological processes (e.g. physical abuse and cardiovascular function), but also share a ' common' epigenetic signature enriched for biological processes related to neural development and organismal growth. A stringent set of sensitivity analyses were also run to identify high-confidence associations. Together, findings lend novel insights into epigenetic signatures of childhood abuse and neglect, point to novel potential biomarkers for future investigation and support a molecular link between maltreatment and poor health outcomes. Nevertheless, it will be important in future to replicate findings, as the use of cross-sectional data and high rates of polyvictimization in our study make it difficult to fully disentangle the shared vs unique epigenetic signatures of maltreatment types. Furthermore, studies will be needed to test the role of potential moderators in the identified associations, including age of onset and chronicity of maltreatment exposure.